The Effect of a Proposed Physical Exercise Program On The Reform Of The Lateral Curve Of The Vertebral Column (Scoliosis) To The Basic Education Pupils(second circle). - Watfe, Olfat; Ali, Nazem; Ahmad, Sarah (Latakia University Journal -Medical Sciences Series, 2018)
The twenty-first century has witnessed a major development in the sports science and physical exercise. Hence the study aimed to identify the impact of the proposed program of physical exercise on the reform of (Scoliosis) of basic education pupils, the research has been conducted on a sample of 6 students, the researcher used the experimental method due to its suitability, the program has been applied on average of two lesson weekly (40-45) minutes within twelve weeks, the researcher found that the proposed program of physical exercise designer has a positive effect and led to a significant improvement in the degrees of curves. The researcher recommended the need to use the proposed physical exercise program in physical education classes for the age stage of 13-14 years, and to conduct further studies about early age groups and more stature bending. أثر برنامج مقترح من التمرينات البدنية على إصلاح الانحناء الجانبي للعمود الفقري (الجنف) عند تلاميذ مرحلة التعليم الأساسي (الحلقة الثانية) شهد القرن الحادي والعشرين تطوراً كبيراً في مجال علوم الرياضة والتمرينات البدنية، ولذلك هدفت الدراسة إلى التعرف على أثر البرنامج المقترح من التمرينات البدنية على إصلاح (الجنف) عند تلاميذ مرحلة التعليم الأساسي، حيث جرى البحث على عينة مكونة من 6 تلاميذ، واستخدمت الباحثة المنهج التجريبي نظراً لملائمته لطبيعة هذا البحث،وتم تطبيق البرنامج بمعدل درسين أسبوعياً حيث زمن الوحدة (40-45 د) على مدى 12أسبوع، وتوصلت الباحثة إلى أن البرنامج المقترح من التمرينات البدنية المصمم له أثر إيجابي وأدى إلى تحسن كبير في درجات الانحرافات. وأوصت الباحثة بضرورة استخدام برنامج التمرينات البدنية المقترح في دروس التربية البدنية للمرحلة العمرية 13-14 سنة، وإجراء المزيد من الدراسات إلى فئات عمرية مبكرة وانحرافات قوامية أكثر.